A floral rangoli outside a Koli home - Mumbai Archive Project Team (Jio Institute, 2024)
A floral rangoli made from marigolds, roses, frangipani, and jasmine. Worli Koliwada, like many other old neighbourhoods in Mumbai, is characterized by narrow, winding lanes and closely packed houses. Despite the narrowness, these lanes serve as common spaces where residents come together to decorate during festivals.